2006
DOI: 10.4102/curationis.v29i3.1092
|View full text |Cite
|
Sign up to set email alerts
|

Primigravidae’s knowledge about obstetric complications in an urban health centre in Malawi

Abstract: Pregnant women in Malawi receive information about pregnancy, labour and delivery during routine antenatal visits. This study aimed to explore knowledge of obstetric complications amongst primigravidae attending an urban health centre in Blantyre, Malawi. A descriptive study design was used. Recognition of obstetric complications in pregnancy, during labour and after delivery and actions that participants would take if they developed any complications in pregnancy and after delivery were explored. Actions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…This finding is in agreement with previous research, which found that educated women have better pregnancy outcomes than uneducated women [1,5,6,20]. This difference probably reflects improved understanding of different health issues, better exposure to information resources, and better decision-making [20][21][22]. The effect of spousal education level might be related to the degree of support and help offered to wives, which clearly makes a difference, as reported by other studies [5].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is in agreement with previous research, which found that educated women have better pregnancy outcomes than uneducated women [1,5,6,20]. This difference probably reflects improved understanding of different health issues, better exposure to information resources, and better decision-making [20][21][22]. The effect of spousal education level might be related to the degree of support and help offered to wives, which clearly makes a difference, as reported by other studies [5].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the majority of women in the current study perceived themselves as knowledgeable about obstetric danger signs and symptoms, yet their actual level of awareness was low. Similar findings were reported by other studies of women interviewed after receiving pregnancy care, indicating a lack of awareness about pregnancy danger signs and symptoms [14,[20][21][22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding knowledge, this study showed only 113(26.8%) of respondents were knowledgeable on danger signs during pregnancy. From those spontaneously mentioned knowledge of danger signs during pregnancy; only 319 (75.6%) mentioned vaginal bleeding, which is high compared to the study done in Malawi 62% [16], whereas very high when compared to studies in Adigrat town, North [3] and in Robe wereda, Arise zone [13].…”
Section: Discussionmentioning
confidence: 70%